Organophosphate esters in total suspended particulates of an urban city in East China. (December 2016) - Ren, Guofa; Chen, Zheng; Feng, Jialiang; Ji, Wen; Zhang, Jin; Zheng, Kewen; Yu, Zhiqianng; Zeng, Xiangying
Abstract: Organophosphate esters (OPEs) are ubiquitous contaminants in the environment, but little is known on the occurrence and distribution of OPEs in the background atmosphere of urban environments. In this study, air samples were collected from two sites in the city of Shanghai, a typical fast developing metropolitan of East China, for investigating the concentration levels, composition profiles, potential sources and human health risk to OPEs. The annual average (median) values of total suspended particulates ΣOPEs concentrations were 19.4 (16.6) and 6.6 (4.4) ng/m 3 for the sub-urban (BS) and urban (XJH) sampling sites, respectively. The ΣOPEs concentrations at BS were significantly higher than those at XJH (P < 0.01), suggesting that more local sources of these compounds in the sub-urban area. The composition profile for ΣOPEs concentrations was different between the two sites, possibly because they originated from different sources. At BS, the dominated OPEs profile was TPhP followed by TCPP and TCEP > TDCPP > TBP > TCP, accounting for 37.0%, 19.6%, 15.8%, 11.8%, 11.0% and 4.2% of the ΣOPEs, respectively. Comparatively, chlorinated OPEs (TCEP, TCPP, and TDCPP) were major contributors to ΣOPEs concentrations at XJH, with the sum of all three chlorinated OPEs concentrations comprising 69.0% of the ΣOPEs. Based on the measured data in the present study human daily intake of each OPEs through particulate inhalation were estimated using a Monte Carlo simulation and the preliminary exposure assessments suggested a low risk of OPEs via inhalation in Shanghai. Highlights: OPEs were measured in TSP over 1 year at two sampling sites in Shanghai. ΣOPEs at the sub-urban site were amongst the highest concentrations yet reported. Composition profile for ΣOPEs concentrations was different between the two sites. Human exposures to the OPEs via inhalation were estimated in Shanghai.